Whitewashing the nation: racist jokes and the construction of the African 'other' in Greek popular cinema. (4th May 2017) - Kompatsiaris, Panos
ABSTRACT: This article explores representations of race in three Greek popular films of the 1970s and 1980s. The portrayal of African characters in these films is antagonistically positioned in relation to the dominant, 'whitewashed' Greek national narrative which relies on the nineteenth century idea that Greece is the progenitor of European civilization. Often masquerading itself as 'just a joke', the discourse of these films narrates the African Other as lacking in terms of culture, intelligence and beauty – the three central categories upon which the idea of the 'white supremacy', according to Cornell West, is historically constructed in modernity. Tightly woven with this idea (largely introduced in Greece by the leading European powers), these films enunciate explicitly colonial viewpoints in a country that was neither a colonial power nor at the geopolitical center of the European project. The article argues that the racialized representations of these films are an effect of appropriating the Eurocentric idea of historicism, where the 'progress' and 'backwardness' of groups and nations are measured according to how effectively they perform the values of modernity.